The effects of primary care on breast cancer mortality and incidence among Medicare beneficiaries. Issue 16 (15th May 2013) - Fisher, Kate J.; Lee, Ji‐Hyun; Ferrante, Jeanne M.; McCarthy, Ellen P.; Gonzalez, Eduardo C.; Chen, Ren; Love‐Jackson, Kymia; Roetzheim, Richard G.
<x xml:space="preserve">Abstract</x> BACKGROUND Primary care physician (PCP) services may have an impact on breast cancer mortality and incidence, possibly through greater use of screening mammography. METHODS The authors conducted a retrospective, 1:1 matching case‐control study using the Surveillance, Epidemiology, and End Results (SEER)‐Medicare–linked database to examine use of PCP services and their association with breast cancer mortality and incidence. SEER cases representing the 3 outcomes of interest (breast cancer mortality, all‐cause mortality among women diagnosed with breast cancer, and breast cancer incidence) were matched to unaffected controls from the 5% Medicare random sample. Conditional logistic regression was used to examine associations between physician visits and breast cancer outcomes while controlling for other covariates. RESULTS Women who had 2 or more PCP visits during the 24‐month assessment interval had lower odds of breast cancer mortality, all‐cause mortality, and late‐stage breast cancer diagnosis compared with women who had no PCP visits or 1 PCP visit while adjusting for other covariates, including mammography and non‐PCP visits. Women who had 5 to 10 PCP visits had 0.69 times the odds of breast cancer mortality (95% confidence interval, 0.63‐0.75), 0.83 times the odds of death from any cause having been diagnosed with breast cancer (95% confidence interval, 0.79‐0.87), and 0.67 times the odds of a late‐stage breast cancer diagnosis (95% confidence interval, 0.61‐0.73) compared with those who had no PCP visits or 1 PCP visit. CONCLUSIONS The current findings suggest that PCPs play an important role in reducing breast cancer mortality among the Medicare population. Further research is needed to better understand the impact of primary care on breast cancer and other cancers that are amendable to prevention or early detection. Cancer 2013;119:2964‐72. © 2013 American Cancer Society.